Normal serum IgE levels and eosinophil counts exhibited during Strongyloides stercoralis infection. Issue 1 (February 2017) - Higashiarakawa, Miwa; Hirata, Tetsuo; Tanaka, Teruhisa; Parrott, Gretchen; Kinjo, Tetsu; Naka, Hidekatsu; Hokama, Akira; Fujita, Jiro
Abstract: Infections with parasites, such as Strongyloides stercoralis, typically cause elevated levels of serum immunoglobulin E (IgE) and eosinophils; however, co-infection with human T cell lymphotropic virus type 1 (HTLV-1) can cause lower levels of serum IgE during S . stercoralis infection. We conducted this study to determine whether serum IgE levels and eosinophil counts could also be related to other patient characteristics or symptoms. Between 1991 and 2014, we measured and compared the symptoms of 237 patients and evaluated serum IgE levels and eosinophil counts of 199 patients who were infected with S . stercoralis at the Ryukyu University Hospital and the Nishizaki Hospital. Medical records were reviewed and blood samples were taken before treatment with the anthelminthic, ivermectin, 2 weeks following the first dosage, and 2 weeks following the second dosage. Commonly reported symptoms included abdominal pain, diarrhea, and general fatigue. Serum IgE levels were found to be normal in patients co-infected with HTLV-1. Additionally, females and patients younger than 70 years old exhibited normal serum IgE levels when infected with S . stercoralis . No factor included in our analysis was found to affect eosinophil counts. Serum IgE levels can remain within the normal range for some patients infected with S . stercoralis . Therefore, physicians should not eliminate S . stercoralis infection from the differential diagnosis solely according to findings of normal or low IgE levels. Highlights: We investigated specific symptoms of patients infected with S . stercoralis . We studied factors affecting serum IgE levels and eosinophil counts. Females or younger patients infected with S . stercoralis had normal IgE levels. No factor affected eosinophil counts.